Evaluation of osteogenic properties of a novel injectable bone-repair material containing strontium in vitro and in vivo - Liu, Lishuang; Hou, Sha; Xu, Guangya; Gao, Jingjing; Mu, Junyu; Gao, Min; He, Jianrong; Su, Xiaoyu; Yang, Zheng; Liu, Yi; Chen, Tengzhuo; Dong, Zhihong; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: This study aims to develop and evaluate the biocompatibility and osteogenic potential of a novel injectable strontium-doped hydroxyapatite bone-repair material. Methods: The properties of strontium-doped hydroxyapatite/chitosan (Sr-HA/CS), hydroxyapatite/chitosan (HA/CS) and calcium phosphate/chitosan (CAP/CS) were assessed following their preparation via physical cross-linking and a one-step simplified method. Petri dishes containing Escherichia coli and Staphylococcus epidermidis were inoculated with the material for in vitro investigations. The material was also co-cultured with stem cells derived from human exfoliated deciduous teeth (SHEDs), to assess the morphology and proliferation capability of the SHEDs, Calcein-AM staining and the Cell Counting Kit-8 assay were employed. Osteogenic differentiation of SHEDs was determined using alkaline phosphatase (ALP) staining and Alizarin Red staining. For in vivo studies, Sr-HA/CS was implanted into the muscle pouch of mice and in a rat model of ovariectomy-induced femoral defects. Hematoxylin-eosin (HE) staining was performed to determine the extent of bone formation and defect healing. The formation of new bone was determined using Masson's trichrome staining. The osteogenic mechanism of the material was investigated using Tartrate-resistant acid phosphatase (TRAP) staining and immunohistochemical studies. Results: X-ray diffraction (XRD) and energy-dispersive spectroscopy (EDS) showed that strontium was successfully doped into HA.The Sr-HA/CS material can be uniformly squeezed using a syringe with a 13% swelling rate. Sr-HA/CS had a significant antibacterial effect against both E. coli and S. epidermidis (p<0.05), with a stronger effect observed against E. coli. The Sr-HA/CS significantly improved cell proliferation and cell viability in vitro studies (p<0.05). Compared to CAP/CS and CS, Sr-HA/CS generated a substantially greater new bone area during osteoinduction experiments (p<0.05, p<0.001). The Sr-HA/CS material demonstrated a significantly higher rate of bone repair in the bone defeat studies compared to the CAP/CS and CS materials (p<0.01). The OCN-positive area and TRAP-positive cells in Sr-HA/CS were greater than those in control groups (p<0.05). Conclusion: A novel injectable strontium-doped HA bone-repair material with good antibacterial properties, biocompatibility, and osteoinductivity was successfully prepared.